BUILDING A MODEL OF THE ANTAGONISTIC GAME OF CHOOSING THE STRATEGY OF FOREIGN ECONOMIC ACTIVITY IN THE CONDITIONS OF DIGITALIZATION - Kulish , Damir (Socio-economic relations in the digital society, 2023)
The purpose of the study is to build a model of the antagonistic game of choosing the strategy of the FEA in the conditions of digitalization. To do this, approaches to the use of Game Theory will be explored. The economic and mathematical apparatus and its application for the strategy of foreign economic activity are considered. This study allows us to determine whether Game Theory is a suitable analytical tool for foreign economic activity-oriented decision-making. In this context, through strategic interdependence games, FEA is associated with making decisions to determine whether to collaborate or compete, innovate or emulate in order to create innovative advantages in the company. It has been found that sometimes our economic decisions are influenced by the decisions of third parties; To understand how these decisions are made and which is the best among several alternatives, game theory arises. The study of game theory in economics will define a game as an abstraction of a specific economic situation. One or more solutions will be suggested, and the author will try to demonstrate which strategies correspond to the equilibrium in the presented game. Game theory cases are often represented graphically using matrices to better understand the reasoning of the participants. Companies use game theory not only to set prices but also to determine when and in which market to conduct FEA and predict competitive decisions. Therefore, the theory of games was applied to foreign exchange for different markets. In order to use this theory, it is necessary to have information about other players, their advantages, and limitations. It consists in achieving a balance of benefits for all. When all players have made a decision and if changing it makes them feel worse, a Nash equilibrium is said to be reached.